Methods of Lightning Protection for the PV Power Plant - Tan, Pi Hua; Gan, Chin Kim (2013)
This paper presents the comparison between air terminal lightning Pole and Early Streamer Emitter lightning Pole in a Photovoltaic (PV) Power Plants. The installation of an external lightning protection system is crucial for power plants to minimize PV system damages. Two different lightning systems were installed to two different PV technology Power Plant systems. The respective system performances were compared in terms of total energy generated and energy yield. The key findings suggest that the air termination lightning pole is suitable for a solar power plant particularly a Thin Film or Crystalline PV power plant system that will result in lower losses compared to the Early Streamer Emitter lightning pole for the PV Power Plant system. This is caused by the shadow of lightning poles that drops on the PV modules to increase solar cell temperature and reduce power generation. Malaysia has one of highest occurrences of lightning activities in the world. Thus, it is essential for PV power plants to have adequate protection from damage and power generation losses.